STUDY OF THE ANTICONVULSANT POTENTIAL OF LEAVES OF CLITORIA TERNATEA LINN. IN PENTYLENETETRAZOLE AND MAXIMUM ELECTROSHOCK SEIZURE INDUCED-CONVULSIONS IN EXPERIMENTAL ANIMALS - Lahon, Joonmoni; Phukan, Swopna; Sharma, Upama (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objectives: To study the anticonvulsant potential of leaves of Clitoria ternatea Linn. in maximal electroshock seizure (MES) and pentylenetetrazole (PTZ)-induced convulsion in experimental animals. Methods: The anticonvulsant potential of the ethanolic extracts of C. ternatea Linn. (EECT) was tested in the MES and PTZ models, seizures were induced, respectively, by delivering electroshock of 50 mA for 0.2 s via a pair of transauricular electrodes using an electro-convulsiometer and by injecting 80 mg/kg intraperitoneally PTZ. For MES model, parameters measured were the duration of hindlimb tonic extension (HLTE), total recovery time, and percentage protection. For the PTZ model, parameters measured were the duration of time taken for the onset of clonic convulsions, duration of clonic convulsions, percentage reduction of clonic phase, and the mortality percentage. Results and Observation: The EECT at both the test doses (200 mg/kg and 400 mg/kg) reduced the duration of HLTE and total recovery time, and increased the percentage protection from MES-induced convulsions, suggesting a dose-dependent anticonvulsant effect of EECT on MES-induced seizures. The extract also produced a dose-dependent anticonvulsant effect on PTZ-induced seizures in albino mice as suggested by prolongation of the latency of clonic convulsion, reduction in the duration of convulsion and seizure score. Conclusion: The present study concludes that the EECT leaves have an anticonvulsant effect on PTZ and MES-induced convulsion in albino mice. Keywords: Antiepileptic, Clitoria ternatea Linn., Ethanolic extract, Maximal electroshock, Pentylenetetrazole, Seizure score.